If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3v+20=5(v+2)
We move all terms to the left:
3v+20-(5(v+2))=0
We calculate terms in parentheses: -(5(v+2)), so:We get rid of parentheses
5(v+2)
We multiply parentheses
5v+10
Back to the equation:
-(5v+10)
3v-5v-10+20=0
We add all the numbers together, and all the variables
-2v+10=0
We move all terms containing v to the left, all other terms to the right
-2v=-10
v=-10/-2
v=+5
| -2x+4=(2)^x+1 | | 2x^2–24x+92=22 | | x+(5/x)=4 | | 4(x+5)=-8x-28 | | 4(m-6)=12 | | 13/11=9/u | | 49m-6=12 | | 28=4(u+4)-6u | | 6^(5x)+4=22 | | (6x-12)/(5x+15)=0 | | -3y/2=-15 | | -6/7=-2y | | -2w+5w+15w=-4 | | -7t-5t=-2 | | -6=3/4u | | -4y/7=-24 | | 3m-14m=6 | | -7y+33=5(y-3) | | -2(u+4)=-4u-22 | | 11=12^2-x^2/4 | | 15-c/20=22 | | 6y+48=-2(y-4) | | -6(u+2)=6u-24 | | 20a-15a^2=0 | | (m+4)m=121 | | d/19+4=5 | | -2k-2=4 | | X1=0.1,x2=1.8 | | 8(2x-3)-5=11 | | -10-6v=-4 | | (6x+22°)=48 | | 8r-2r=1-34 |